THE EFFICACY OF DOORVADI GHRIT IN THE MANAGEMENT OF PARIKARTIKA ( FISSURE IN ANO) - Barkade Pallavi S; Kalmegh Manjusha S (International Journal of Applied Ayurved Research, 2017)
Fissure in Ano ( Parikartika) is a vertical tear or an elongated longitudinal ulcer in the long axis of stratified squamous epithelium of the lower anal canal. Ancient text couldn’t give a brief idea about this condition. Mainly it has been described as complication of Bastikarma and Atisar. It is so named in which sharp cutting pain is felt in the anus. For that conservative treatment fails, and modern surgical treatment of choice is again has limitations such as faecal incontinence. Hence, Doorvadi Ghrita having effective Vranaropan & Dahaprashaman, Shonit sthapan property i.e. it relieves burning sensation quickly. So we modified a method of Local Application is conceived for this study.